ANALISI MODEL STRUKTURAL IMAGE TERHADAP PENINGKATAN DAYA TARIK PERGURUAN TINGGI X DI SEMARANG - Setiawan, Andi (STIE Totalwin Semarang, 2012)
This article is a research for the researchers in the field of marketing communications. This article was formulated based on the notes and important facts found in the field. Facts on which the cause of the low enrollees choose the College X in Semarang, one cause is indicated due to the ineffectiveness of the model during the campaign that was conducted by the College X in Semarang. This article attempts to explore further the factors that led to choose a college appeal X. Formulation variables and indicators refer to previous research studies. A model has been developed and three hypotheses have been formulated to address the problem of this research. The sampling technique is quota sampling. Respondents from this study of 100 respondents, where respondents were the College X in Semarang. Data analysis tool used is a structural equation modeling (SEM) in AMOS 16.0 program. The results of data analysis of this study suggest a third model and research hypotheses can be accepted. Managerial implications of giving advice to focus on the influence of information technology services support the quality of the image and appeal of the College X in Semarang.